In-vitro bioactivity evaluation and non-targeted metabolomic analysis of green tea processed from different tea shoot maturity. (December 2021) - Xu, Chunhui; Liang, Lu; Yang, Tianming; Feng, Lei; Mao, Xuejin; Wang, Yuanxing
Abstract: The chemical quality and biochemical properties of green tea processed from different tea shoot maturity has largely remained unexplored thus far. Total phenolic content, and total flavonoid content decreased during tea shoot maturation. Three in-vitro bioactivities, namely α-glucosidase and pancreatic lipase inhibitory and antioxidant activity showed a similar changing trend. A significant correlation between TPC and TFC, and these bioactivities was found. Non-targeted metabolomic analysis revealed that green tea processed from different tea shoot maturity had obvious differences. Variable importance analysis and S-plot gave 32 characteristic metabolites responsible for the discrimination of different green teas. Orthogonal partial least square analysis was used calculate the correlation coefficient between each characteristic metabolite and the values of three in-vitro bioactivities. Several important differential bioactive metabolites were obtained using the above analysis. This study explored the metabolic change in green tea during the process of tea shoot ripening, thus providing unique tea quality information for green tea production. Highlights: TPC, TFC, and α-glucosidase and pancreatic lipase inhibitory and antioxidant activity decreased during tea shoot maturation. TPC and TFC contributed significantly to these three in-vitro bioactivities. Non-targeted metabolomic successfully separated green tea processed from different tea shoot maturity. 32 characteristic metabolites closely related to tea shoot growth were found. Several important differential bioactive metabolites were obtained using OPLS analysis.